Tayma, Saudi-Arabien. Ergebnisse der Keramikauswertung. Die Arbeiten der Jahre 2009 bis 2018 - Tourtet, Francelin; Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2018)
Pottery analysis in the framework of the Saudi-German project at the oasis of Tayma (Northwest Arabia) resulted in the reconstruction of a more than 3000 year long history of production technology and usage. Whereas the beginning of ceramic production at Tayma has been dated to the late 4th / early 3rd millennium BC, it is 3rd to 4th century AD contexts marking the end of this sequence. Stylistic and archaeometric analyses of the material demonstrated that besides strong local and regional characteristics, the pottery from Tayma mirrors the socio-economic and cultural connectedness of the oasis, in particular to the Southern Levant, but also to the larger Eastern Mediterranean, as evidenced by the presence of numerous non-local productions.